REPUTASI DAN PROFESIONALISME AUDITOR SEBAGAI DETERMINAN KUALITAS AUDIT (Studi Empiris Pada Kantor Akuntan Publik Di wilayah Kota Makassar) - Dewi Anggraeni; Ulfa Rabiyah (Jurnal Akuntansi Kompetif, 2026)
This study aims to determine the influence of auditor reputation and professionalism on audit quality. This study addresses the need for more empirical evidence regarding an auditor's audit quality. Agency theory serves as the basis for the model's conceptual framework. The study respondents were auditors from 35 public accounting firms in Makassar. The researcher used multiple linear regression to characterize the influence of independent variables on the dependent variable to analyze the hypotheses. The results of this study found that audit quality is influenced by an auditor's reputation and professionalism